Using Fear and Anxiety Related to COVID-19 to Predict Cyberchondria: Cross-sectional Survey Study - Wu, Xue; Nazari, Nabi; Griffiths, Mark D (JMIR Publications, 2021)
BackgroundStudies have highlighted that fear and anxiety generated by COVID-19 are important psychological factors that affect all populations. There currently remains a lack of research on specific amplification factors regarding fear and anxiety in the context of the COVID-19 pandemic. Despite established associations between anxiety sensitivity, intolerance of uncertainty, and cyberchondria, empirical data investigating the associations between these three variables, particularly in the context of the COVID-19 pandemic, are currently lacking. Urgent research is needed to better understand the role of repeated media consumption concerning COVID-19 in amplifying fear and anxiety related to COVID-19. ObjectiveThis study investigated the associations between fear of COVID-19, COVID-19 anxiety, and cyberchondria. MethodsConvenience sampling was used to recruit respondents to participate in an online survey. The survey, which was distributed via social media and academic forums, comprised the Cyberchondria Severity Scale, Fear of COVID-19 Scale, Coronavirus Anxiety Scale, Anxiety Sensitivity Index, and Intolerance of Uncertainty Scale. Multiple mediation analyses were conducted using structural equation modeling. ResultsA total of 694 respondents (males: n=343, females: n=351) completed the online survey. The results showed that fear and anxiety generated by COVID-19 predicted cyberchondria (fear: β=.39, SE 0.04, P<.001, t=11.16, 95% CI 0.31-0.45; anxiety: β=.25, SE 0.03, P<.001, t=7.67, 95% CI 0.19-0.32). In addition, intolerance of uncertainty and anxiety sensitivity mediated the relationship between fear and anxiety generated by COVID-19 with cyberchondria. In a reciprocal model, the standardized total effects of cyberchondria on fear of COVID-19 (β=.45, SE 0.04, P<.001, t=15.31, 95% CI 0.39-0.51) and COVID-19 anxiety (β=.36, SE 0.03, P<.001, t=11.29, 95% CI 0.30-0.41) were statistically significant, with moderate effect sizes. Compared to males, females obtained significantly higher scores for cyberchondria (t1,692=-2.85, P=.004, Cohen d=0.22), COVID-19 anxiety (t1,692=-3.32, P<.001, Cohen d=0.26), and anxiety sensitivity (t1,692=-3.69, P<.001, Cohen d=0.29). ConclusionsThe findings provide a better understanding of the role of COVID-19 in amplifying cyberchondria. Based on these results, cyberchondria must be viewed as a significant public health issue. Importantly, increasing awareness about cyberchondria and online behavior at both the individual and collective levels must be prioritized to enhance preparedness and to reduce the adverse effects of current and future medical crises.